Stuart Woods' Smolder [large type] - Battles, Brett; Woods, Stuart (Woods, Stuart. Stone Barrington novel, 2024)
"Finally enjoying some downtime in Santa Fe, Stone Barrington agrees to attend an art exhibit with a dear friend. There, he encounters an intriguing woman who is on the trail of a ring of art thieves. Always one to please, Stone offers his help. From Santa Fe to Los Angeles, it quickly becomes clear that her investigation has links to Stone--particularly to rare Matilda Stone art, his mother's paintings. And when old grudges come to light, Stone is forced to reckon with a familiar enemy. Stone must act fast before whoever is out to get him finally closes in on him . . . for good"--